Peran Pemerintah Kabupaten Jepara Dalam Menyelesaikan Konflik Pertambangan Batuan pada Tanah Bengkok di Desa Tunggulpandean - Agung Syaifuddin; Sulistyowati .; Dzunuwanus Ghulam Manar (Journal of Politic and Government Studies, 2015)
This research aims to understand role of Jepara Regency Government on resolve mining conflict, which was taking place between residents with Modin Zulfa of Tunggulpandean village. The underlying causes of the conflict is when the Land asset of Modin Zulfa Tunggulpandean was made as mine rock. Mining companies had no official permission and had potentially damaging surrounding environment. This study also explains the steps taken by the Government on preventing similar conflicts that took place in the Tunggulpandean village.This research using descriptive qualitative on data collection. The subject this research is the actors involved in conflict mining rocks in land of Tunggulpandean Village asset, representatives of the Tunggulpandean residents, Modin Zulfa land owner, The Government of Tunggulpandean Village, The Government of Jepara Regency, and Lakpesdam NU Jepara as LSM. Technical data collection relied on interviews, documentation, and literature, analyzed through reduction data, editing and conclusion.Research concluded that the District Jepara does not perform their functions optimally. This can be seen from time needed in solving the conflict. In the future, The Government of Jepara regency have to intensively and optimize their function, especially the role of  mining agencies related like Bina Marga, Pengairan & ESDM, BPMPPT, BLH, and Satpol PP. So at a time will come there is no longer conflicts such as happened in Tunggulpandean village.